PENURUNAN KADAR DETERGEN (LAS) DAN FOSFAT DENGAN METODE BIOFILTER AEROB-ANAEROB DAN ANAEROB-AEROB - Syafiyyah Dzikra Mirandri; Yayok Suryo Purnomo (EnviroUS, 2021)
Laundry waste is identical to organic contaminants in the form of detergents (LAS) and phosphates, if these materials are disposed of directly into the environment and accumulate, it will cause a eutrophication phenomenon. Biofilter is a biological treatment with attached culture bacteria, in the process the media is a place for bacteria to attach and grow. Combined biofilter is a combination of an anaerobic with an aerobic processing or vice versa. The purpose of this study was to determine the effectiveness and optimalization of laundry waste treatment in reducing levels of detergent (LAS) and phosphate using a combination biofilter method. The variables treated in this research were the combination of aerobic-anaerobic biofilter system with anaerobic-aerobic biofilter and sampling time (2, 4, 6, 8, and 10 hours). Variations in the combination of aerobic-anaerobic biofilter systems can reduce detergent levels (LAS) by 97.08% and phosphate by 85.39%, anaerobic-aerobic biofilter systems can reduce detergent levels (LAS) by 97.19% and phosphates by 82.51 %. The sampling time variable resulted in a reduction efficiency of detergent levels (LAS) of 88.95 - 98.83%, and phosphate of 84.82 - 86.96% stably. Keywords: Aerobic-Anaerobic Biofilters, Anaerobic-Aerobic Biofilters, Laundry Wastewater, LAS Detergent, Phospat